Effect of Ethanol Extract of Suruhan Leaves (Peperomia Pellucida L. Kunth) on Blood Sugar Levels and Macroscopic Wounds in Male White Rats of the Wistar Strain (Rattus norvegicus) Diabetic Ulcer Model - Hakim, Enggrek Pelita; Siahaan, Jekson Martiar; Anto, Endy Juli; Eyanoer, Putri Chairani (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: High blood sugar levels can cause diabetes mellitus (DM), which currently means more than one in 10 adults live with diabetes, with the biggest risk factor being obesity. Wound healing in DM patients will be hampered and increase the incidence of diabetic ulcers in Indonesia by 12% and the risk of developing diabetic ulcers by 55.4%. Diabetic ulcers and gangrene cases in Indonesia are the most common cases found in hospitals. Mortality due to ulcers and gangrene ranges from 17-23%, while the amputation rate ranges from 15-30%. Therapeutic potential in the treatment of diabetic ulcers is possessed by suruhan leaves which have anti-inflammatory, antipyretic, antimicrobial and anticancer effects, as well as having analgesic effects. Subjects and Method: A total of 30 male white rats of the Wistar strain (Rattus norvegicus) were divided equally into control groups, negative control (STZ induction 40mg/kgBW), positive control (STZ induction 40mg/kgBW with metformin 50mg/kgBW/day), treatment group I (STZ induction 40mg/kgBW with ethanol extract of shrike leaves 40mg/kgBW), and treatment group II (STZ induction 40mg/kgBW). kgBB with ethanol extract of 80 mg/kgBB leaves). Next, blood sugar levels (KGD) and macroscopic examination of diabetic ulcer wounds are carried out. Data were analyzed using the Anova test. Results: The lowest blood sugar levels (183.83 ± 11.39), the lowest wound area (6.89 ± 0.86), and the highest percentage of excision wound healing (89.67 ± 1.37) were found in the positive control group. There was a significant relationship between groups of mean blood sugar levels, between groups of wound area, and between groups of healing percentage of excision area (P<0.05). Conclusion: Administration of ethanol extract of suruhan leaves (Peperomia pellucida L. Kunth) had an effect on reducing blood glucose levels and healing diabetic ulcer wounds in STZ-induced diabetic ulcer model mice.